Managing Operational Risk Of Laycan Using Fmea (Failure Mode And Effetct Analysis) – A Case Study Of Tarahan Port - Qoshoshi, Ahsanul; Yudoko, Gatot (UNIVED Press, 2026)
PT Bukit Asam Tbk (PTBA) is a leading coal mining enterprise with a vital role in supplying energy for both domestic consumption and export markets. One of the company’s major challenges lies in managing laycan schedules, which can trigger operational risks, intensify port congestion, and hinder the coal loading process. This study aims to identify operational risks associated with laycan that lead to demurrage and to propose strategies to mitigate these risks at Tarahan Port. The research applies a gap analysis framework supported by Failure Mode and Effect Analysis (FMEA). Data were collected through both primary and secondary sources. Primary data involved focus group discussions designed with FMEA to assess severity, frequency, and detection levels, with insights from thirteen informants: eight from the distribution division, one port supervisor, and four operational support staff. Secondary data were drawn from historical records spanning 2023–2024. The analysis incorporated FMEA and Root Cause Analysis (RCA). Findings revealed 25 root causes using the 5 Why method. The top risks included loading delays at jetty 3, simultaneous vessel arrivals, domestic jetty queues, export documentation delays due to surveyor systems. Recommendations emphasize addressing urgent loading bottlenecks, implementing phased solutions, enhancing cross-team coordination, and ensuring continuous monitoring.